Risk assessment and psychosocial interventions for suicidal patients. (20th June 2013) - Chesin, Megan; Stanley, Barbara
Abstract : Objectives: Suicide is a leading cause of death in the USA. Although factors elevating long‐term risk for suicide are known and include bipolar disorder, signs of imminent suicide risk are difficult to study and not well specified. Acute risk determinations must be made to determine the appropriate level of care to safeguard patients. To increase safety among at‐risk patients in the short term and to decrease risk over time, psychosocial interventions to prevent suicide have been developed and tested in acute care and outpatient settings. Methods: A narrative review of studies of imminent risk factors for suicide, suicide risk decision‐making, and psychosocial suicide prevention interventions was conducted. Results: Although some long‐term risk factors of suicide have been established, accurate identification of individuals at imminent risk for suicide is difficult. Therefore, prevention efforts targeting individuals at high suicide behavior risk discharging from acute care settings tend to be generic and focus on psychoeducation and supportive follow‐up contact. Data regarding the effectiveness of brief interventions (i.e., those not requiring more than one individualized treatment session) are mixed, showing better outcomes in the shorter term and when the incidence of suicidal behavior or ideation is the outcome. With respect to longer‐term suicide prevention interventions (i.e., those with a minimum of ten sessions), Dialectical Behavior Therapy has the largest evidence base. Conclusions: To improve suicide prevention efforts, more rigorous study of imminent risk factors and psychosocial interventions is needed. Adaptations specific to individuals with bipolar disorder are possible and needed.